성인의 원부모와의 애착 표상과 낭만적 애착 및 아동기 양육 경험과의 관계에 대한 연구 - 진미경; Mi Kyoung Jin (한국놀이치료학회지(놀이치료연구), 2009)
본 연구에서는 성인의 원부모와의 애착 표상과 성인기 낭만적 애착과의 관련성과, 아동기 양육경험과 부모에 대한 애착 표상의 관련성, 아동기 양육 경험과 성인기 낭만적 애착의 관련성을 살펴보았다. 본 연구를 위해 대인관계 향상 집단 프로그램에 참여한 대학교 2, 3학년 학생들 24명과 부모자녀 관계 증진 프로그램에 참여한 어머니 8명이 참여하였다. 부모와의 애착 표상을 평가하기 위해 성인애착면접(Adult Attachment Interview)이 이루어졌고, 낭만적 애착 관계를 평가하기 위해 Bartholomew와 Horowitz의 관계유형 질문지(Relationship Questionnaire)가, 아동기 양육 경험을 평가하기 위해 PBI(The Parental Bonding Instrument)가 사용되어졌다. 자료 분석은 교차분석과 독립표본 t-검증을 실시하였다. 그 결과 25명(78%)이 부모에 대한 애착 표상과 낭만적 애착 관계의 일치를 보였다. 아동기 경험한 양육경험이 부모에 대한 애착 표상과 성인기 낭만적 애착 관계와 관련이 있는 것으로 나타났다. This study aimed to examine the three kinds of relations; one is between attachment representation to parents in childhood and romantic attachment in adulthood, another is between caregiving experiences in childhood and attachment representation to parents, and the other is between caregiving experiences in childhood and romantic attachment in adulthood. To that end, the subjects of this study include 24 college students in the sophomore and junior years who participated in an interpersonal relationship-improving program and eight mothers who participated in a parent-child relationship-improving program. The adult attachment interview was conducted to evaluate the attachment representation to parents, the Relationship Questionnaire of Bartholomew and Horowitz was used to estimate the romantic attachment, and the PBI (The Parental Bonding Instrument) was used to assess the caregiving behaviors experienced in childhood. The crosstab and independent t-test were also performed in data analysis. In result, it was found that 25 people (78%) of those subjects showed the consistency between parent attachment representation and romantic attachment. Therefore, it was concluded that the caregiving behaviors experienced in childhood has a relation with the parent attachment representation and the romantic attachment in adulthood.